Factors Affecting the Intensity of Community Involvement in Family Empowerment and Welfare Programs in Aceh Tamiang Regency - Syafnela Rahmawaty; R Hamdani Harahap; Heri Kusmanto (Budapest International Research and Critics University, 2022)
The involvement of women in the PKK is about how women can be active to achieve family welfare through involvement in the PKK so that the existence of women is recognized by all parties. The results of this empowerment can later be seen from an increase in the quality of family life and an increase in the economy of the family itself. To increase women's participation in the PKK, it is necessary to accelerate the PKK through PKK reform so as to optimize family welfare. The purpose of this research is to analyze demographic factors, approach factors, and social capital factors that affect the intensity of community involvement in the Family Welfare Empowerment Program (PKK) in Aceh Tamiang District. This research method uses mixed methods (combination) with a sequential approach. The size of the sample used the Taroyamane/Slovin formula with a precision of 10%, with a 95% confidence level, so the sample was obtained as many as 88.37 Dasa Wisma PKK groups in Manyak Payed District, Aceh Tamiang Regency which were then rounded up to 90 Dasa Wisma groups. The data collection technique carried out by the researcher used several methods, namely interviews, documentation studies, and a list of questions. Data Analysis Techniques The research technique used in this study is the Multiple Linear Regression Test technique, and the hypothesis testing of the Ftest and R2 tests and the partial test (t-test). Research results Simultaneously there is a positive and significant influence between Social Demography, Empowerment Approach and Social Capital on the Intensity of Community Involvement in the Family Welfare Empowerment Program (PKK) with the results of the regression coefficient test is 2,956 and the T test is 2.190 with a significant level of 0.031 (α <0.05). Thus the hypothesis can be accepted.